Pengaruh Diversitas, Inklusi dan Kreatifitas Kerja terhadap Kinerja Pegawaidi Perwakilan BKKBN Provinsi Sulawesi Barat - Fahdiansyah, Dudi; Aqil, Muhammad; Ramli S, Ramli S; Abdullah, M Said (Journal of Management Branding, 2025)
This study aims to understand how diversity, inclusion, and work creativity affect employee performance at the BKKBN Representative of West Sulawesi Province. The approach used was quantitative, with multiple linear regression analysis techniques. The entire research population amounted to 58 people, and of these, 30 respondents were selected based on purposive sampling technique with the criteria: female gender and maximum age of 55 years. The results of the analysis show that together, the three variables have a significant effect on employee performance, with a coefficient of determination (R²) of 0.587. This means that most of the variation in performance can be explained by diversity, inclusion and work creativity. However, separately, only work creativity has a significant effect on employee performance. Diversity and inclusion have not shown a statistically meaningful impact. These findings emphasize the important role of individual innovation in driving bureaucratic performance, as well as the need to strengthen diversity and inclusion practices to contribute significantly to organizational productivity